Colostrum feeding practice and associated factors among mothers who come for postnatal care to Asella referral and teaching hospital, Arsi Zone, South-East Ethiopia - Haji, Gisha; Agero, Gebi; Eshete, Amde; Hasan, Abdurahman; Hiko, Ahmed (Frontiers in Medicine, 2025)
BackgroundEvery day throughout the world more than 4,000 infants and young children die because colostrum feeding was not initiated within an hour of birth as recommended by the World Health Organization (WHO)/United Nations Children’s Fund. Even though breastfeeding is common in Ethiopia, the widespread belief that colostrum feeding causes morbidity and mortality among neonates still exists.ObjectiveTo assess the colostrum feeding practice and It’s associated factors among mothers who come for Post-natal care at Asella Referral and Teaching Hospital, Asella Town, Southeast Ethiopia from November 20, 2023, to January 25, 2024.MethodThis study employed an institutional-based cross-sectional study among 301 surveyed postnatal care mothers from November 20, 2023, to January 25, 2024. Systematic random sampling was employed to select study participants. A pretest was performed to check the reliability and clarity of the study questionnaires. The tool to examine the practice of colostrum feeding and related aspects was modified from earlier studies. The collected data were input into Epi Info version 7.2.5.0 and exported to SPSS version 26 for analysis. Bivariate and multivariable logistic regression analyses were used to identify variables associated with the practice of colostrum feeding. The variables with significant association were identified based on p-value < 0.05.ResultsIn this study, 301 study participants took part, with a 99% response rate. The mean age of mothers was found to be 27.13 ± 5.46. This study’s overall prevalence of practice was 57.8% (95% CI, 52.2–63.35). Being Urban residence (AOR = 4.05, 95%CI: 2.18–7.52), health education counseling (AOR = 4.31, 95%CI: 1.27–10.73), and favorable attitude toward colostrum milk (AOR = 6.64, 95% CI: 3.61–12.2) were factors significantly associated with colostrum feeding practice.Conclusion and recommendationsIn comparison to WHO recommendations, the study area had a low rate of colostrum feeding practice. Additionally, this study also identified factors associated with maternal colostrum feeding practice level such as urban residence, counseling on timely initiation of breastfeeding during antenatal care, and good maternal attitude toward colostrum feeding. Therefore, Health education dissemination should be given to postnatal mothers regarding the importance of colostrum feeding.